Functional safety a straightforward guide to applying IEC 61508 and related standards - Smith, David J. 1943 June 22- (Elsevier Butterworth-Heinemann, 2004)
A practical guide to designing and assessing safety-critical systems to international standards.
Keywords: Industrial safety -- Standards -- European Union countries.; Process control -- Standards -- European Union countries.; Manufacturing processes -- Safety measures -- Standards -- European Union countries.; elektronické knihy; electronic books